Elevated levels of cell-free NKG2D-ligands modulate NKG2D surface expression and compromise NK cell function in severe COVID-19 disease - Fernández-Soto, Daniel; García-Jiménez, Álvaro F.; Casasnovas, José M.; Valés-Gómez, Mar; Reyburn, Hugh T. (Frontiers in Immunology, 2024)
It is now clear that coronavirus disease 19 (COVID-19) severity is associated with a dysregulated immune response, but the relative contributions of different immune cells is still not fully understood. SARS CoV-2 infection triggers marked changes in NK cell populations, but there are contradictory reports as to whether these effector lymphocytes play a protective or pathogenic role in immunity to SARS-CoV-2. To address this question we have analysed differences in the phenotype and function of NK cells in SARS-COV-2 infected individuals who developed either very mild, or life-threatening COVID-19 disease. Although NK cells from patients with severe disease appeared more activated and the frequency of adaptive NK cells was increased, they were less potent mediators of ADCC than NK cells from patients with mild disease. Further analysis of peripheral blood NK cells in these patients revealed that a population of NK cells that had lost expression of the activating receptor NKG2D were a feature of patients with severe disease and this correlated with elevated levels of cell free NKG2D ligands, especially ULBP2 and ULBP3 in the plasma of critically ill patients. In vitro, culture in NKG2DL containing patient sera reduced the ADCC function of healthy donor NK cells and this could be blocked by NKG2DL-specific antibodies. These observations of reduced NK function in severe disease are consistent with the hypothesis that defects in immune surveillance by NK cells permit higher levels of viral replication, rather than that aberrant NK cell function contributes to immune system dysregulation and immunopathogenicity.